Morphological variation of Stratiodrilus circensis (Polychaeta, Histriobdellidae) from a new host, Aegla leptodactyla (Crustacea, Anomura, Aeglidae) with identification of its type host species - Daudt, Luiz C.c.; Amato, José F. R. (Zootaxa, 2007)
Stratiodrilus circensis Steiner & Amaral, 1999, ectocommensal of anomuran crabs Aegla leptodactyla Buckup & Rossi, 1977 (New Host Record), is first recorded for the State of Rio Grande do Sul, southern Brazil, with some considerations on the observed morphological variation and the identification of its type host species. Thirty crabs were examined, 70% of which were positive for S. circensis. Intensity of infestation varied from 1 to 41 (arithmetic mean 13.3; SD 10.4). Eleven specimens of S. circensis from Aegla schmitti Hobbs III, 1979, collected from Rio Carvalho, tributary of Rio Piraquara, State of Paraná, (the type locality), were also examined. Differences in total body length, length of antennae, cirri, conical ventral lobes, and tubercles were found between the specimens described here, the specimens described in previous works, and the specimens from A. schmitti from Rio Carvalho. The geographical distribution of S. circensis is discussed